Effects of different cooking methods on the antioxidant activities of Hericium erinaceus (BULL.: FR.) pers. / Siti Amalina Mohamad Jalani - Siti Amalina , Mohamad Jalani (2017)
All living organisms require ongoing oxidation process where the carbohydrates, proteins and fats are metabolised by oxygen in order to generate energy. However, this continuous oxidation process in human system generates the production of unfavourable natural by-products called free radicals. Free radicals are highly reactive and are produced in large numbers and when the radicals outnumbered the healthy molecules, the imbalance will affect the antioxidant defence mechanism. Human body has been equipped with antioxidant system that protects the body against free radicals attacks. Apart from fruits, vegetables, whole grains as well as vegetable oil, the consumption of mushrooms in daily diet has become tremendously popular. The increasing awareness of mushrooms benefits among consumer provides significant reason for scientific study to be carried out in terms of their antioxidant properties. One of the mushrooms that are of interest is Hericium erinaceus or Lion’s Mane Mushroom. The aim of the study was to investigate the effect of different cooking methods (boiling, microwaving, steaming and pressure-cooking) on antioxidant capacities of H. erinaceus. Besides total phenolic content determination, the antioxidant assay conducted were 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay, reducing power assay, inhibition of lipid peroxidation of buffered egg yolk and Trolox equivalent antioxidant capacity (TEAC) assay. Both fresh and oven-dried samples subjected to 5 minutes of steaming significantly increased the DPPH radical scavenging activity. The reducing powers of all fresh and oven-dried samples increased steadily with the increasing concentrations of 0.5-5.0 mg/ml. In general, the cooking did not significantly enhance the lipid peroxidation inhibition for all tested samples. The same results were depicted in the TEAC assay where cooking did not affect the antioxidant activity significantly except for the samples submitted to 5 minutes of microwaving (fresh) and 5 minutes of pressure-cooking (oven-dried) by which their antioxidant activity was significantly (p < 0.05) increased. Most of the cooked samples investigated showed an elevated amount of total phenolic content compared to the respective uncooked sample. A weak correlation between the antioxidant activity and total phenolic content of samples tested indicated that the antioxidant activity of the mushroom was not due to the content of phenolic compounds. Since there were limited numbers of similar studies conducted, further study has to be carried out involving the same species of mushroom cooked under the same conditions for the purpose of data verification.